ANALISIS SEKTOR KUNCI DALAM PEREKONOMIAN PROVINSI RIAU: ANALISIS INPUT-OUTPUT - Khairunnas '; Djaimi Bakce; Susi Edwina (Fakultas Pertanian, Universitas Riau, 2014)
Determining key sector is important because can be pass economic development of Riau. This research use linkage analysis by utilizing the indices forward linkage and backward linkage obtained from the multiplier matrices of Input-Output Table.The results of the analysis find eight sectors as the key sectors. This is indicated by their value ofbackward linkage and forward linkage which are higher than the average linkage of the whole economic sectors. Those eight sectors are rice, soy bean, another beans, other plantation crops, palm oil and animal oil, pulp, crumb rubber and smoke rubber, transportation and communication. These commodities should be developed so that can be increase economic of Riau, but does not rule out the possibility of the another sectors to be developed. Research in inter-sectoral linkage may obtain the strength of one particular sectorin influencing other sectors for actively contributing to the Riau economy. However, I-O analysis possessed limitation that prevents the key sectors to be used for long-term policy consideration. Consequently, agriculture development should not continuously depend on the key sectors. More over, it should also develop the potency of other sectors so that agriculture sector would become the key sector of the Riau development as a whole, not partially.